Development of Powtoon Based Science Learning Media in Elementary Schools - Bungawati Bungawati; Ervi Rahmadani* (Jurnal Pendidikan Sains Indonesia, 2023)
The multimedia use of learning media in elementary school in Soppeng district has not been made up for because 56,4% teachers still using on textbooks as learning media. The purpose of this study was to develop science learning media using powtoon in elementary schools. This study uses a type of development research, namely research and development. The product developed in this study is a learning media based on natural science material about ecosystems for fifth grade. The theme chosen is theme 5 sub-theme 1 learning 1. This research was carried out in 3 schools located in Lilirilau District, Soppeng Regency including SDN 254 Mappatongai, SDN 125 Marale, SDN 112 Burecceng. The subjects of this study were the fifth grade students, totaling 21 students. The data collection procedure was carried out based on the 5 steps of the ADDIE model. Data collection techniques used are questionnaires and media validation. The data obtained were analyzed using qualitative and quantitative approaches. The results of this study resulted in a product in the form of Powtoon based learning media. The results of the validation test by material experts with an average percentage of 95.25% in the very valid category, the results of validation by media experts with an average percentage of 93% in the very valid category while the average feasibility test obtained 75% in the feasible category. The learning media developed is suitable for use by teachers and students as learning media